The Main Directions and Prospects of The Transformation of Social Ideas - Nabiyev Mansur Jamkhur ugli (Periodica Journal, 2023)
One of the main directions of the transformation of social ideas is the harmonization of the national idea of the main idea of our independence and independence, which is determined by the reflection of the national idea of the transformation of social ideas. On the chosen path of any independent state, the existence of social ideas that embody the life of society and the identity of its people suggests that this country is a social state to a greater extent.
Keywords: nationality; transformation; democracy